Neural tube defects and folate: case far from closed - Blom, Henk J. (2006)
Neural tube closure takes place during early embryogenesis and requires interactions between genetic and environmental factors. Failure of neural tube closure is a common congenital malformation that results in morbidity and mortality. A major clinical achievement has been the use of periconceptional folic acid supplements, which prevents ~50–75% of cases of neural tube defects. However, the mechanism underlying the beneficial effects of folic acid is far from clear. Biochemical, genetic and epidemiological observations have led to the development of the methylation hypothesis, which suggests that folic acid prevents neural tube defects by stimulating cellular methylation reactions. Exploring the methylation hypothesis could direct us towards additional strategies to prevent neural tube defects.